Intertextuality As An Art Of Narration: An Analysis Of The Novels Of Bapsi Sidhwa (International Journal of Food and Nutritional Sciences, 2022)
This paper entitled “Intertextuality as an art of Narration: An Analysis of the novels of Bapsi Sidhwa” examines how Sidhwa makes use of intertextuality as an art of narration in her novels. It is a technique of narration which makes the readers aware of the concept of universality of literary themes in literature. It enables the readers to develop their reading and writing skills. It also unveils the authors knowledge in various literatures belong to the world. Sidhwa’s effective use of intertextuality in her novels makes the readers to be aware of the literary styles and methods employed by the famous writers who belong to the different parts of the world. She has made use of intertextuality in almost all her novels to provide depth to her writings.